Flotillins in the intercalated disc are potential modulators of cardiac excitability. (January 2019) - Kessler, Elise L.; van Stuijvenberg, Leonie; van Bavel, Joanne J.A.; van Bennekom, Joëlle; Zwartsen, Anne; Rivaud, Mathilde R.; Vink, Aryan; Efimov, Igor R.; Postma, Alex V.; van Tintelen, J. Peter; Remme, Carol A.; Vos, Marc A.; et al.
Abstract: Background: The intercalated disc (ID) is important for cardiac remodeling and has become a subject of intensive research efforts. However, as yet the composition of the ID has still not been conclusively resolved and the role of many proteins identified in the ID, like Flotillin-2, is often unknown. The Flotillin proteins are known to be involved in the stabilization of cadherins and desmosomes in the epidermis and upon cancer development. However, their role in the heart has so far not been investigated. Therefore, in this study, we aimed at identifying the role of Flotillin-1 and Flotillin-2 in the cardiac ID. Methods: Location of Flotillins in human and murine cardiac tissue was evaluated by fluorescent immunolabeling and co-immunoprecipitation. In addition, the effect of Flotillin knockout (KO) on proteins of the ID and in electrical excitation and conduction was investigated in cardiac samples of wildtype (WT), Flotillin-1 KO, Flotilin-2 KO and Flotilin-1/2 double KO mice. Consequences of Flotillin knockdown (KD) on cardiac function were studied (patch clamp and Multi Electrode Array (MEA)) in neonatal rat cardiomyocytes (NRCMs) transfected with siRNAs against Flotillin-1 and/or Flotillin-2. Results: First, we confirmed presence in the ID and mutual binding of Flotillin-1 and Flotillin-2 in murine and human cardiac tissue. Flotillin KO mice did not show cardiac fibrosis, nor hypertrophy or changes in expression of the desmosomal ID proteins. However, protein expression of the cardiac sodium channel NaV 1.5 was significantly decreased in Flotillin-1 and Flotillin-1/2 KO mice compared to WT mice. In addition, sodium current density showed a significant decrease upon Flotillin-1/2 KD in NRCMs as compared to scrambled siRNA-transfected NRCMs. MEA recordings of Flotillin-2 KD NRCM cultures showed a significantly decreased spike amplitude and a tendency of a reduced spike slope when compared to control and scrambled siRNA-transfected cultures. Conclusions: In this study, we demonstrate the presence of Flotillin-1, in addition to Flotillin-2 in the cardiac ID. Our findings indicate a modulatory role of Flotillins on NaV 1.5 expression at the ID, with potential consequences for cardiac excitation. Highlights: Flotillin-1 and Flotillin-2 are present in the cardiac intercalated disc Flotillin knockout decreases protein levels of the sodium channel NaV 1.5 Knockdown of Flotillin-2 and -1/2 by siRNAs decreases the peak inward sodium current (INa ) Flotillins seem to affect cardiac excitability